Marcadores discursivos interacionais no português da Ilha de Santiago, Cabo Verde - Veloso, Emilly Sampaio Silva (2023)
The discourse markers are linguistic elements that assist in the process of construction of the utterance, highlighting what is implicit and explicit in the oral and/or written text. Although proven their importance for the development of discourse and the vast amount of works that deal with these markers, these linguistic forms continue to be stigmatized and absent from normative grammar as a category. Most research on the subject focuses mainly on Brazilian and European Portuguese, with few studies on discursive markers in Portuguese spoken on the African continent, specifically in Portuguese spoken in Cape Verde. With this, this dissertation aims to analyze and the interactional discursive markers present in the oral discourse of Cape Verdean Portuguese, specifically on the island of Santiago, in three social groups: students, teachers and politicians. For this, we had as a parameter the defining traits proposed by Risso, Silva and Urbano (2015). We used the data collected from the field research, carried out during graduation, with 26 interviews and the transcription of 08 semi-structured interviews of Lopes' thesis (2011). The results point to a high occurrence of interactive discursive markers in the group of students, being the group with the lowest diversity of these elements and the lowest occurrence with politicians being the group that uses the greatest diversity of markers.